Study on Landscape Processes with Special Reference to Landslides in Lele Watershed, Central Nepal - Manandhar, Indra Narayan; Khanal, Narendra Raj (Himalayan Review, 2011)
Available with fulltext. Key words: Nepalese landscape; Landslide; Watershed; Geomorphological hazards The Himalayan Review Vol. 24-28 1993-1997 Page: 22-35 Uploaded date: 15 June, 2011